The Gossypium anomalum genome as a resource for cotton improvement and evolutionary analysis of hybrid incompatibility. Issue 11 (6th September 2021) - Grover, Corrinne E; Yuan, Daojun; Arick, Mark A; Miller, Emma R; Hu, Guanjing; Peterson, Daniel G; Wendel, Jonathan F; Udall, Joshua A
Abstract: Cotton is an important crop that has been the beneficiary of multiple genome sequencing efforts, including diverse representatives of wild species for germplasm development. Gossypium anomalum is a wild African diploid species that harbors stress-resistance and fiber-related traits with potential application to modern breeding efforts. In addition, this species is a natural source of cytoplasmic male sterility and a resource for understanding hybrid lethality in the genus. Here, we report a high-quality de novo genome assembly for G. anomalum and characterize this genome relative to existing genome sequences in cotton. In addition, we use the synthetic allopolyploids 2(A2D1) and 2(A2D3) to discover regions in the G. anomalum genome potentially involved in hybrid lethality, a possibility enabled by introgression of regions homologous to the D3 ( Gossypium davidsonii ) lethality loci into the synthetic 2(A2D3) allopolyploid.